Delirium and Mortality in Coronavirus Disease 2019 (COVID-19) – A Systematic Review and Meta-analysis. (July 2021) - Pranata, Raymond; Huang, Ian; Lim, Michael Anthonius; Yonas, Emir; Vania, Rachel; Kuswardhani, Raden Ayu Tuty
Highlights: Delirium was associated with mortality in both pooled unadjusted and adjusted model Meta-regression indicates that the association does not vary with age, sex, hypertension, diabetes, and dementia Heterogeneity might be due to confounders and different assessment tools Every 1 mg/L increase in CRP was significantly associated with 1% increased delirium risk Abstract: Introduction: Older adults are indisputably struck hard by the coronavirus disease 2019 (COVID-19) pandemic. The main objective of this meta-analysis is to establish the association between delirium and mortality in older adults with COVID-19. Methods: Systematic literature searches of PubMed, Embase, and Scopus databases were performed up until 28 November 2020. The exposure in this study was the diagnosis of delirium using clinically validated criteria. Delirium might be in-hospital, at admission, or both. The main outcome was mortality defined as clinically validated non-survivor/death. The effect estimates were reported as odds ratios (ORs) and adjusted odds ratios (aORs). Results: A total of 3, 868 patients from 9 studies were included in this systematic review and meta-analysis. The percentage of patients with delirium was 27% [20%, 34%]. Every 1 mg/L increase in CRP was significantly associated with 1% increased delirium risk (OR 1.01 [1.00. 1.02], p=0.033). Delirium was associated with mortality (OR 2.39 [1.64, 3.49], p<0.001; I 2 : 82.88%). Subgroup analysis on delirium assessed at admission indicate independent association (OR 2.12 [1.39, 3.25], p<0.001; I 2 : 82.67%). Pooled adjusted analysis indicated that delirium was independently associated with mortality (aOR 1.50 [1.16, 1.94], p=0.002; I 2 : 31.02%). Subgroup analysis on delirium assessed at admission indicate independent association (OR 1.40 [1.03, 1.90], p=0.030; I 2 : 35.19%). Meta-regression indicates that the association between delirium and mortality were not significantly influenced by study-level variations in age, sex [reference: male], hypertension, diabetes, and dementia. Conclusion: The presence of delirium is associated with increased risk of mortality in hospitalized older adults with COVID-19.